The Role of IPNU IPPNU in Implementing Adolescent Moral Behavior in Bansari Village Temanggung - Fauziah, Fida Nur; Sakir, Sakir; Fuadi, Salis Irvan (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
Â The social situation of the community lately is increasingly worrying, various kinds of events in the social environment are increasingly troubling. The decline in moralvalues and lack of solidarity has occured in the lives around us. A lot of juvenile delinquency is happening everywhere, drus use is rampant, free sex is starting to become a lifestyle, watching porn videos among teenagesr is common, brawls are normal, not being wise in social media such as spreading hoaxes, hate speech, slander more intense and so on. Therefore, this research aims to 1. find out how to inculcate morality in youth through IPNU IPPNU activities in Bansari Village, Temanggung 2. to find out how the results of the implementation of IPNU IPPNU activities in inculcating morality in youth in Bansari Village, Temanggung 3. This thesis uses the type of field research or field research with a qualitative approach. The research subjects are daily administrators, members, adolescent and community leaders. To obtain the necessary data, the authors use the techniques of observation, interviews, and documentation. Data analysis of data reduction, presentation, and conclusion. The results showed that IPNU IPPNU carried out various activities in an effort to instill morality, namely by carrying out work programs, in activities carried out by IPNU IPPNU teenagers would be equipped with knowledge and insight about knowledge, not only in terms of organization but also knowledge about socializing well which can be applied directly. The results of the implementation of IPNU IPPNU activities in the cultivation of adolescent morality are categorized as good, it can be seen from the awareness of teenagers to learn religious knowledge, behavior becomes better. The supporting factors in inculcating morality through IPNU IPPNU activities are self-motivation, parental support, a qualified environment, and the approach of the IPNU IPPNU management and the inhibiting factors are the individual himself, funds and parental permission.